Islamic Educational Values on the Mappogau Sihanua Karampuang Local Wisdom of Sinjai District - Mustamin Mustamin (Indonesian Journal of Multidisciplinary Science, 2023)
This article discusses the values ??of Islamic education in the local wisdom of the Mappogau Sihanua Karampuang traditional ceremonial tradition, Sinjai Regency. The main issues raised in this study are how the process of the traditional ceremony of Mappogau Sihanua Karampuang, Sinjai Regency, how are the values ??of Islamic Education contained in the traditional ceremony of Mappogau Sihanua Karampuang, Sinjai Regency. It is a field research, which belongs to qualitative approach. The author conducted it in the location and directly got involved with the object under study. From research conducted by researchers within a month of research on the values of Islamic education on the local wisdom of the Mappogau Sihanua Karampuang custom, it can be concluded that the tradition  of the Mappogau Sihanua  Karampuang traditional ceremony is a big feast every year. In the Mappogau Sihanua tradition, there are several ritual processes that contain Islamic educational values, namely the value of solidarity/mutual cooperation, the value of ukhuwah, the value of art, and shadaqah.